Le don de la revue Assurances à l’École des Hautes Études Commerciales - Parizeau, Robert (Assurances)

(untitled) (HEC Montréal, 1996)
Founded in 1932 by Mr. Gérard Parizeau, Assurances has been a major contributor to the growth and development of Canadian expertise in the field of insurance. To secure the continuity of this journal, Sodarcan inc., its present owner, has taken the decision to donate Assurances to I'École des Hautes Études Commerciales. The journal will now be published under the aegis of the newly-established Risk Management Chair to be held by Professor Dionne. Remi Moreau will become the journal's Chief Editor and act as a link between the university and the insurance industry. As Assurances begins a new chapter in its life, I wish to thank Remi Moreau and Murielle Laramée for their commitment and the quality of their work. I am also grateful to the many collaborators for sharing their valuable expertise and the advertisers for their support. Lastly, I wish to thank the journal's faithful readership for having been with us throughout the years.